Abatement of radioiodine in aqueous reprocessing off-gas - Greaney, Allison T.; Ngelale, Randy O.; Bruffey, Stephanie H.; Martin, Leigh R. (Frontiers in Chemistry, 2023)
The reprocessing used nuclear fuel (UNF) releases volatile fission and activation products, including 129I, into the off-gas of a processing plant. Mitigation of the release of vapor phase radionuclides is necessary for meeting regulatory requirements in the United States and other countries. In an aqueous reprocessing plant, volatile radioiodine could be present in several forms, depending on the chemistry of the process used. Inorganic iodine will be the predominate species in any shearing or voloxidation pretreatment off-gas and dissolver off-gas (DOG). Organic iodides such as CH3I, C4H9I, and C12H25I have been proposed to be generated during solvent extraction; thus, these species must be captured from the vessel off-gas (VOG). The abatement of inorganic and organic iodide species to meet United States regulatory requirements has been demonstrated in laboratory experiments using Ag-based solid sorbents. The data presented in this paper includes the effect of gas composition (e.g., the presence of water vapor and NOx), iodine speciation (I2, CH3I, C4H9I, C12H25I), and sorbent bed parameters (e.g., temperature, sorbent age) on complete iodine capture on Ag-mordenite in an aqueous reprocessing plant.